ANALISIS USAHATANI PALA DI KAMPUNG TALAWID KECAMATAN KENDAHE KABUPATEN KEPULAUAN SANGIHE - Nolvi Sanggel; Olly E. H. Laoh; Grace A.J. Rumagit; Ellen G. Tangkere (Universitas Sam Ratulangi, 2014)
ABSTRACTNolvi Sanggel. Analysis Nutmeg Farming in Talawid Village, Kendahe Sub District, Sangihe Islands Regency. Under the guidance O. Esry H. Laoh, as a Chairman, Grace A. J. Rumagit, and Ellen G. Tangkere as Members.The objective of this research is to analyze nutmeg farming in Talawid Village, Kendahe Sub District, Sangihe Islands Regency, Benefits of this research is to provide input and information materials for the development of nutmeg farming to related institution in order to increase their income.The method used in this study was